Plan de negocio para la producción y comercialización de agua medicinal embotellada a base de sábila en el cantón La Maná, 2023. - Chiluisa Chicaiza, Freddy Ramiro (2024)
Considering that natural medicine is based on the use of natural ingredients and methods that respect and work in harmony with nature. The general objective of this research was to design a business plan for the production and marketing of bottled medicinal water based on aloe vera in the canton of La Maná in response to the increase in the population's consumption of natural alternatives to improve their health and quality. of life. To fulfill this purpose, bibliographic research was used by collecting theoretical information and field research to obtain relevant data on supply and demand through the technique of surveys directed at business owners and families in the canton. The Mana. The market study revealed that the supply of aloe water was 265,248 liters and a demand of 1,258,054.56 liters, obtaining an unsatisfied demand of -992,805.56 liters. In addition, the technical feasibility could be determined because the optimal location and resources for its operation are available. In addition, this study described the organizational, functional and legal aspects for the operation of the microenterprise. The economic study reflected a net profit of $90,055 for the first year, the cash flow allowed us to calculate a NPV of $471,115.42, an IRR of 67.23%, and a ROA of 38.73%. With the development of the project, the owners and consumers of the product benefit and therefore impacts were reflected in the economic, technical and social spheres.